Assessment of internal parasite infection in horses from various farm types in the western area of Libya - Asem Ramadan Amar Mohamed; Ahmed Imbayyah Abdulqadir Ashteebah; Abdeulmajid Hossein Mohammed Khapoli (African Journal of Advanced Pure and Applied Sciences, 2025)
The study was carried out in 2023 (from April to October) in the western area of Libya. Horses from individual and horse racing stables with varying housing, feeding, and field care methods (including Arabian and Thoroughbred horses) had their feces sampled. 450 horses were analyzed (380 mares, 15 geldings, and 55 stallions). Among the 300 horses from individual farms, 143 (47.6%) had protozoan infections, and 111 (37%) had gastrointestinal parasite infections. Thirty-one (20.6%) and 29 (19.3%) of the 150 horses from racing farms had protozoan infections and gastrointestinal parasite infections, respectively. Most horses from individual farms and racing farms were infected with the gastrointestinal parasite Moniezia spp. and the protozoan cryptosporidium parvum. The total number of horses from individual farms free of infection from gastrointestinal parasites was 189 (63%), and horses free of infection from racing farms were 121 (80.6%). While free from protozoa in individual farms 157 (52.3%) and from racing farms 119 (79.3%). In some horses, eggs of Trichostongyliode spp. Parascaris equorum, and tapeworm of Anoplocephala spp., were found in the individual, and racing farms. The horses from both individual and racing farms were infected with other protozoa: Blantidum coli, Entamoeba coli, Eimeria spp. Individual farms had a higher number of infected horses than the horse racing stable farms.